Pengangguran dalam Perspektif Islam - Yolanda Kirana Sari; Agung Rizkiyan; Apriza Apriza (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
Unemployment is a significant economic problem that can affect society's well-being. In an Islamic economic perspective, unemployment is viewed through the lens of social justice, equitable distribution of wealth, and other sharia principles. The causes of unemployment in an Islamic economy include unfair distribution of wealth, lack of relevant education and skills, injustice in the conventional interest-based financial system, and economic and political instability. To overcome unemployment, Islamic economics offers solutions through the effective implementation of zakat, alms and waqf, the use of profit-sharing-based financial instruments such as mudharabah and musyarakah, as well as investment in education and skills training. The government also plays an important role in creating an environment that supports job creation through fair and stable policies. Encouraging entrepreneurship through training and access to capital is also an effective strategy in reducing unemployment. This holistic approach not only aims to reduce unemployment levels, but also to create a more just and prosperous society in accordance with Islamic economic principles.